(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses the choice of Kazakhstan insurance system in the health sector. The analysis of the problems of the formation of a stable system of insurance in the market of medical services. The experience of countries with highly developed health care system and the ways to overcome the problems in the Republic of Kazakhstan. The article uses a comparative legal, historical and legal analysis of the development of public health. As a result, the conclusions about the need to introduce into the national health system of market regulation mechanisms and the formation of a more adapted to the modern realities of management. The findings can be used to develop new ways to improve the country’s health system.